Triglyceride-rich very low density lipoproteins (VLDL) are independently associated with insulin secretion in a multiethnic cohort of adolescents - Tricò, Domenico (Diabetes Obes Metab, 2018)
Excess insulin secretion and hyperinsulinemia contribute to the progression of type 2 diabetes. However, the mechanisms leading to insulin hypersecretion remain largely unknown. Based on our preliminary data, we examined whether triglycerides and very low-density lipoprotein (VLDL) are independently associated with insulin secretion, and whether the ethnicity/race modulates these associations. Fasting triglycerides and VLDL were measured in a multiethnic cohort of 630 non-diabetic adolescents. Insulin secretion, β-cell function parameters, insulin sensitivity and insulin clearance were estimated through a 3-h OGTT. Metabolic assessments were repeated after 2 years in 239 subjects. Triglycerides and triglyceride-rich VLDL (large and medium size fractions) were associated with both basal and glucose-stimulated insulin secretion, after adjustment for age, sex, ethnicity, BMI z-score, plasma glucose, and insulin sensitivity. Ethnicity per se had an impact on lipid profile and β-cell function, but did not modulate the effect of triglycerides/VLDL on insulin secretion. At follow-up, changes in triglyceride levels were proportional to changes in insulin secretion. These findings support the hypothesis that hypertriglyceridemia is an important stimulus for β-cell insulin release in youths under both fasting and fed conditions.